Comparison of two methods of cyclones simulation: semi‐empiric model and CFD. Example of a specific cyclone design. Issue 1 (3rd April 2012) - Bardin‐Monnier, N.; Altmeyer, S.; Schreiber, V.; Marecat, A.
ABSTRACT The aim of this work is to design a cyclone separator, which could reach the highest separation efficiency for fine and low‐density particles (1–10 µm) and air‐flow rates between 10 and 100 L/min. The first part of the study is dedicated to the design, thanks to cyclone software developed by PROGEPI, Nancy, France. It uses classical models and does not take into account the dispersed phase fraction, but allows giving a first approach of the cyclone geometry. Results lead to a Lorenz geometry and pressure drop lower than 10 KPa for 100 L/min. The separation efficiency is never lower than 75% for 2‐µm particles at 50 L/min. In the second part, a computational fluid dynamics study via fluent is conducted in order to determine the performances of the device, thanks to the particle trajectories simulations. Results show that for the higher flow rate (100 L/min), a separation efficiency of 60% is reached for 1‐µm particles. For a lower flow rate (10 L/min), this cyclone is not satisfying because no 1‐µm particles are separated. This study shows that these two approaches are quite complementary in order to reach the most accurate design. Copyright © 2012 Curtin University of Technology and John Wiley & Sons, Ltd.